Combined Lacrimal Passage Probing and Tobramycin/Dexamethasone Ophthalmic Ointment Infiltration: A Minimally Invasive Surgical Procedure for Incomplete Nasolacrimal Duct Obstruction. Issue 36 (September 2015) - Xu, Jianjiang; Hong, Jiaxu; Sun, Xinghuai; Liu, Zuguo; Mashaghi, Alireza; Inomata, Takenori; Lu, Yi; Li, Yimin; Wu, Dan; Yang, Yujing; Wei, Anji; Zhao, Yujin; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The optimal treatment strategy for an incomplete nasolacrimal duct obstruction (INDO) is still being debated. The aim of this study is to evaluate the treatment results of combined lacrimal passage probing and tobramycin/dexamethasone ophthalmic ointment infiltration (PIO, Probing and Injection) for INDO. In this retrospective, noncomparative case series, 397 consecutive adult patients with INDO treated at Shanghai Eye, Ear, Nose and Throat Hospital were enrolled. Records of the patients were reviewed. With the help of a modified 23-gauge lacrimal cannula, the PIO surgery was performed for the INDO-identified patients. The main outcome measures were resolution of tearing and complications. The relationship between successful outcome and clinical characteristics was analyzed. The surgery was performed successfully in all of the enrolled cases. No intraoperative complications were found in the procedure. The average follow-up time was 7.9 months. Three hundred patients (75.6%) experienced complete resolution of their symptoms after the surgery. Ninety-seven patients (24.4%) showed a partial improvement (1.8%), no improvement (18.4%), or a worsening of symptoms (4.3%). Of the 97 surgical-failure patients, 90 required silicone intubation or external dacryocystorhinostomy, and 94% were finally resolved. The most common postoperative complications were mild nasal bleeding in 41 patients, drug residues in 12 patients (6 developed the complete obstruction), and a slit punctum in 8 patients. Multivariate logistic regression analysis revealed that unilateral eye onset, not having a discharge at baseline, and not having postoperative drug residues were significant factors determining successful outcome. The PIO surgery is an effective, safe, timesaving, easy-to-perform, and minimally invasive technique for treating INDO.